Penerapan Media Wayang Kartun Dengan Menggunakan Strategi Talking Puppets Dalam Meningkatkan Keterampilan Berbicara Siswa Kelas V SD N Bungasrejo - Sunarlin, Ninik; , Dra. Sri Hartini, S.H, MPd (2017)
The research aims to describe: 1) students 'speaking skills class V SDN Bungasrejo, 2) measures of learning by implementing a media puppet cartoons to train students' speaking skills class V SDN Bungasrejo, 3) Strategy of talking puppets to improve students' speaking skills class V SDN Bungasrejo. This type of research is the Classroom Action Research (CAR) in the discussion using quantitative descriptive. Resource persons from this study is the guardian class V and V grade students of SDN Bungasrejo. Data collection techniques in this study using observation, interview and test. Testing the validity of the data obtained using the triangulation of sources and techniques. Stages of this research using PTK Kurt Lewin in the form of Planning (Planning), Execution (Action), observation (Observing), Reflections (Reflecting). The study results represent an increase of learning outcomes in learning Indonesian on aspects of speaking skills. There are two cycles in this study is the first cycle and the second cycle. In prasiklus completeness percentage is only 60% with an average grade 75.5, then the first cycle an increase in the percentage of completeness 70% with an average of 76.6 and the last class in the second cycle is a significant increase in the percentage of completeness reaches 95 % with an average grade 81.35. In this study proved by applying the puppet media cartoons and puppets talking strategy class V student learning outcomes in learning Indonesian in the aspect of talking increases.